Effectiveness of instrumented gait analysis in interdisciplinary interventions on parents' perception of family-centered service and on gross motor function in children with cerebral palsy: a randomized controlled trial - Christina Esmann Fonvig; Helle Mätzke Rasmussen; Søren Overgaard; Anders Holsgaard-Larsen (BMC, 2020)
Abstract Background Children with cerebral palsy often exhibit an altered gait pattern; however, it is uncertain whether the use of an instrumented gait analysis in interdisciplinary interventions affects the perceived experience of family-centered service (FCS) and/or gross motor function. The aim of this study is to investigate whether individually tailored interdisciplinary interventions, based on an instrumented gait analysis report, has a superior effectiveness on perceived FCS and gross motor function in children with cerebral palsy, compared to 'care as usual' without the use of instrumented gait analysis. Furthermore, to investigate potential associations between perceived FCS and gross motor function improvement with the goal of improving future therapy on gross motor function. Method This is a sequel analysis on tertiary outcome measures from a prospective, single blind, randomized, parallel group study including two groups of 30 children aged 5-8 years with spastic cerebral palsy at Gross Motor Function Classification System levels I-II (n = 60). The intervention group underwent a three-dimensional gait analysis, from which a clinical report was written with recommendations on interdisciplinary interventions, such as physical therapy, orthopedic surgery, orthotics or spasticity management. To assess effectiveness on perceived FCS and gross motor function, at baseline, 26 weeks and 52 weeks, the five domains in the Measure of Processes of Care (MPOC-20) (Enabling and partnership, Providing general information, Providing specific information about the child, Respectful and supportive service, and Coordinated and comprehensive care) and the Gross Motor Function Measurement (GMFM-66) were used as outcome measures. Results No significant differences in between-group change scores in any of the five MPOC-20 domains were observed (p = 0.40-0.97). In favor of the intervention group a significantly higher between-group change score in GMFM-66 (mean difference: 3.05 [95%CI: 1.12-4.98], p = 0.003) after 52 weeks was observed. Conclusion The addition of an instrumented gait analysis report to 'care as usual' did not improve the parents' perceptions of FCS in treatment of children with cerebral palsy. However, superior improvement in the GMFM-66 was observed in the intervention group, suggesting meaningful gross motor function improvement. Trial registration Clinical Trials, NCT02160457 . Registered June 10th 2014.